Fracture Toughness of Cement Mortar Containing High Volume Fly Ash - Ahmed, Shaikh; Maalej, M. (ACI, 2007)
In this paper experimental evaluation on the effect of high volume fly ash as partial replacement of cement on fracture toughness of cement mortar are presented. The fly ash replacement level was 50%, 60% and 70% by weight of cement. Three-point bend notch beams were used to measure the fracture toughness of mortar. Results show that the use of 50% fly ash as partial replacement of cement reduces the fracture toughness values between 38% and 58% compared to that without fly ash. Reduction of compressive strength and Young's modulus in mortar containing 50% fly ash as partial replacement of cement compared to that without fly ash is also observed in this study. The use of 60% and 70% fly ash as partial replacement of cement is found to have negligible effect on the reduction of fracture toughness of cement mortar. Long term effects of high volume fly ash (50% cement replacement) on fracture toughness, compressive strength and Young's modulus of cement mortar are also evaluated in this study. Tests were conducted at 28, 56 and 91 days and at 5, 7, 10 and 12 months. Results show that the rate of increase of fracture toughness of cement mortar containing 50% fly ash with time is very slow. Compressive strength and Young's modulus also increase with time.